SERVANT LEADERSHIP, SPIRITUALITAS TEMPAT KERJA, DAN EMPLOYEE ENGAGEMENT DI FAKULTAS LIBERAL ARTS UNIVERSITAS X [SERVANT LEADERSHIP, WORKPLACE SPIRITUALITY AND EMPLOYEE ENGAGEMENT IN THE FACULTY OF LIBERAL ARTS, UNIVERSITY X] - Adriani Gunawan; Ahmad H Sutawidjaya; Indrawan Tjhin (Polyglot, 2022)
Leadership style can not only shape employee behavior by influencing employee attitudes, such as their satisfaction, commitment, and well-being at work, but also can shape performance such as job involvement through motivational construction. The purpose of this study was to analyze the relationship between servant leadership, workplace spirituality and employee engagement in an analytical-critical manner and comprehensively based on the primary and secondary data available at the Faculty of Liberal Arts, University X. This study used an approach with the research subject of 40 lecturers; permanent, and 5 part time. The data processing method is descriptive method. From the results of the study it can be concluded that servant leadership in FLA has a positive relationship and influence; the state of workplace spirituality in FLA has a positive influence that is built personally (lecturers), and is supported by servant leadership based on the truth of God's Word indicating that the condition of workplace spirituality has good results and  employee engagement in FLA occurs because of the relationship between leaders who apply servant leadership style and Jesus Christ as a role model.Bahasa Indonesia Abstrak: Gaya kepemimpinan tidak hanya dapat membentuk perilaku karyawan dengan mempengaruhi sikap karyawan, seperti kepuasan, komitmen, dan kesejahteraan mereka di tempat kerja, tetapi juga dapat membentuk kinerja seperti keterlibatan kerja melalui konstruksi motivasi. Tujuan dari penelitian ini adalah untuk menganalisis hubungan  antara servant leadership, spiritualitas tempat kerja dan employee engagement secara analitis-kritis dan komprehensif berdasarkan data primer dan data sekunder yang tersedia di Fakultas Liberal Arts, Universitas X. Penelitian ini menggunakan pendekatan kualitatif dengan subjek penelitian 40 dosen tetap dan 5 dosen paruh waktu. Metode pengolahan datanya yaitu metode deskriptif. Dari hasil penelitian diperoleh kesimpulan bahwa servant leadership di FLA memiliki hubungan dan pengaruh yang positif, keadaan spiritualitas tempat kerja di FLA membawa pengaruh yang positif yang dibangun secara pribadi (dosen), dan didukung oleh praksis servant leadership pimpinan fakultas berazaskan kebenaran firman Tuhan yang menunjukkan bahwa kondisi spiritualitas tempat kerja memiliki hasil yang baik serta keadaan employee engagement di FLA terjadi karena adanya keterkaitan antara pimpinan yang menerapkan gaya servant leadership dengan Yesus Kristus sebagai role model.